AVENIR progress and impact assessment: Descriptive report - Muriithi, Cyrus; Ouedraogo, Issa; Chege, Christine; Kinyua, Michael; Nouwodjro, Paul; Diouf, Latyr; Maina, Wilson; Siagbe, Golli (2025)
This assessment of the AVENIR project activities demonstrates significant progress in building climate resilience and improving livelihoods among smallholder farmers in Senegal's Sedhiou and Tambacounda regions. Through its integrated approach combining climate-smart agriculture, economic empowerment, and capacity building (reaching 11,500 beneficiaries, 70% women and youth), the project has achieved measurable impacts across key outcome areas.